Kompetensi Guru Mata Pelajaran Fiqih dalam Mengelola Kelas Terhadap Minat Belajar Siswa - Ahmad Musaddad; Uswatun Hasanah (Nusantara Journal of Islamic Studies, 2022)
As a contribution to Indonesian education, several educational institutions continue to compete in improving the quality of graduates to achieve the standards issued by the government through the National Education Standards (SNP). Likewise, competition between schools under the auspices of the Ministry of Education and Culture and Madrasahs under the auspices of the Ministry of Religion of the Republic of Indonesia. This research uses descriptive qualitative research with a case study approach at Madrasah Aliyah Al-Cholily Sumber kolak Panarukan Situbondo. The results of this study are 1) Teachers of active fiqh subjects arrive early, and always keep their promises to their students; 2) The teacher communicates and knows the character of the students well. 3) The teacher mastered the material well. 4) The teacher is neat. 5) Teachers not only use the concept of textual learning, but also use the concept of contextual learning in delivering material in class. Meanwhile, the teacher's obstacles in managing the class on students' interest in learning are: 1) Students are difficult to manage. This is indicated by the presence of some students who are still frequently in and out of class, and some even do not return to class. 2) Lack of adequate infrastructure in the classroom, such as the absence of an LCD projector that can facilitate teaching and learning activities in the classroom.